(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
This work presents an extension action involving the topic of pesticides. This theme has been extensively developed, both in teaching and extension activities. However, the differential of the action reported here is that it was all planned to be accessible to the deaf and blind communities, working in a dialogic and critical way (according to Paulo Freire) the Brazilian agricultural development model, especially the intensive use of pesticides. From the documentary “Nuvens de Veneno”, accessible materials were created: Libras window in the documentary; chemical structures of the active ingredients printed in 3D and in high relief with inscriptions in Braille and audio-described; and a printed and audio-described leaflet, contextualizing the problems caused to the environment, human and animal health. All this material was used during the activity at the National Science and Technology Week. The action was carried out both in a booth during the event, at the Federal University of Rio de Janeiro, and in the territory of a state school, during classes of chemistry of six high school classes. During the two days of exhibition at the stand, the activity generated interest from a wide range of audiences, from elementary school children, teachers - who took their classes - as well as a group of deaf students. In the school’s territory, the activity moved the classes in a strong way, working on the chemistry of pesticides, social and environmental concerns, including refugee students, with intellectual disabilities, autism and cognitive and intellectual disorders.